PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE RECIPROCAL UNTUK MENINGKATKAN PERCAYA DIRI DAN PRESTASI BELAJAR SISWA (Studi Pada Mata Pelajaran IPS Siswa Kelas VIIA SMP N 3 Kepahiang, Bengkulu) - Rustam Syani (DIADIK, 2020)
This study improves self motivation and social studies learning achievement by using the Reciprocal Cooperative learning model. The design of this study is Classroom Action Research (CAR). Data collection using observation technique, questionnaires and tests. The instruments used were observation sheets, questionnaire sheets and test questions. The research subjects were students of SMP Negeri 3 Kepahiang class VIIa semester 1. The results obtained by cycle I are the confidence of students from class VIIA SMP Negeri 3 Kepahiang an average of Less Criteria with having average scores.Cycle II increased to Good Criteria with having scores above the average. Cycle III increased to Very Good Criteria with having scores above the average. For student achievement reached with an N-gain value of Less Effective in cycle I. Student learning achievement increased by scores with Ngain value of quite effective in the second cycle. Student learning achievement increased by scores with an N-gain effective. From the results of the study it can be concluded that the cooperative learning model of reciprocal learning type can increase the confidence and achievement of social studies students of class VIIA SMP N 3 Kepahiang.